(untitled) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-2-149-157 The article deals with literary riddles and their role in the educational process. Currently, in the teaching methodology, the questions of working on a folk riddle are most fully developed, while the methodology of working on a literary riddle is studied only in separate works. Therefore, the main attention in our work is devoted to the study of literary riddles, their types and methods of correct solving. The use of various types of literary riddles in the educational process, along with folk riddles, allows to build a consistent system of working on riddles in elementary school. We have attempted to reproduce a generalized classification of Lezghin literary riddles, including a methodological aspect. The proposed classification, in combination with the thematic classification, expands the teacher’s opportunities in preparing for work with the puzzle in lessons and extracurricular activities. It has been proven that the use of all types of riddles, especially riddles with comparison and metaphorical riddles, contributes to the development of imagery and metaphorical speech of younger schoolchildren, allows to consciously introduce literary examples, figurative expressions into children’s speech, to inculcate the habit of using metaphors in speech. It is indicated that guessing riddles is an important stage in the development of a child. Key words: Lezghin folklore; folk riddle; literary riddle; method; the development of things